An exploratory study of maternal diabetes and offspring use of dental services-Northern Ireland national cohort study - Anas Salami; Ikhlas El Karim; Fionnuala Lundy; Tom Loney; Michael Donaldson; Ciaran O'Neill (Nature Publishing Group, 2023)
Abstract Introduction A small number of literature has posited a link between prenatal exposure to gestational diabetes mellitus and an increased risk of developmental defects in the enamel of offspring. However, the evidence remains inconclusive. Aims This study examined the relationship between the diabetes status of mothers and the use of dental services by offspring to that pregnancy. Material and methods Anonymised data from a cohort of mothers who carried a child to term in Northern Ireland between 2012 and 2017 and service use by the child were taken from administrative databases from March 2015 to September 2021. Descriptive statistics, differences in means and regression analyses were used to examine the relationship between service use and maternal diabetes status, controlling for covariates. Results In multivariate analyses that controlled inter alia for age and deprivation, diabetes status was negatively related to restoration, extraction, prevention, and total service use. In the analysis of the COVID period, pre-COVID prevention was negatively related to extractions, restorations, prevention and services in general. Conclusion The relationship between maternal diabetic status and aspects of offspring use of dental services was contrary to that suggested in previous studies and warrants more detailed investigation using this valuable data resource.